LASER DRILLING QUALITY OF VARIOUS MATERIALS DEPENDING ON THE LASER BEAM PARAMETERS - Fedotovs, Jānis; Bartkevičs, Jānis; Āboliņš, Artūrs; Narica, Pāvels (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
This research describes Nd:Yag laserbeam drilling in different material types. Experimental part was used to predict the effect of laser drilling parameters including laser beam power and defocusing. In this research was used two material types- aluminium and ceramics